Meningkatkan Kesadaran Masyarakat dalam Pembayaran Pajak Bumi dan Bangunan melalui Inovasi Pelayanan Publik di Kota Surabaya - Kristiandari, Arinda; Soebiantoro, Ugy (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Land and Building Tax (PBB) payments are an important source of income for local governments, including the City of Surabaya. PBB plays a strategic role in supporting the financing of infrastructure development, public services, and as a program that is directly related to the needs of the community. However, in practice, the realization of PBB payments is still faced with the challenge of low taxpayer awareness, especially among the general public who do not fully understand the urgency of PBB payments and how to access services provided by the government. Low levels of tax literacy, limited socialization, and disparities in access to digital technology are some of the main inhibiting factors.  This study was conducted using a qualitative descriptive method through a literature study, analyzing secondary data from literature, government documents, and online information to evaluate the impact of service innovation on increasing taxpayer awareness. Along with the development of information technology and the transformation of public services, the Surabaya City Government through the Regional Revenue Agency (Bapenda) has launched various service innovations to encourage public awareness and compliance in paying PBB. These innovations include digitalization of services through the website pbb.surabaya.go.id and the PBB mobile car program that brings services closer to residents' residential areas. However, the effectiveness of this innovation will not be maximized without increasing public understanding and awareness of their tax obligations.